Soft Composite Gels with High Toughness and Low Thermal Resistance through Lengthening Polymer Strands and Controlling Filler. (3rd November 2022) - Cai, Linfeng; Fan, Jianfeng; Ding, Shengchang; He, Dongyi; Zeng, Xiangliang; Sun, Rong; Ren, Linlin; Xu, Jianbin; Zeng, Xiaoliang
Abstract: Soft gels with high toughness have drawn tremendous attention recently due to their potential applications in flexible electronic fields. The miniaturization and high‐power density of electronic devices require soft gels with both high toughness and low thermal resistance; however, it is difficult to achieve these properties simultaneously. Herein, a simple design strategy is reported for constructing soft (high stretchability of 6.91 and low Young's modulus of 340 kPa), tough (4741.48 J m −2 ) and thermal conductive (low thermal resistance of 0.14 cm 2 K W −1, under 10 psi pressure) polydimethylsiloxane/aluminum composite gel. This is realized by precisely lengthening polymer strands between the chemical cross‐linked points and controlling the aluminum content in the composite gels. The symbiosis of this combination involves: lengthening the polymer strands facilitates its unfolding to increase the softness and intrinsic toughness; the thermally conductive spherical aluminum enables low thermal resistance and increases the intrinsic toughness and stress dissipation. By utilizing this gel as a thermal interface material, effective heat dissipation is demonstrated in electronic devices operating under high‐power conditions over numerous cycles. These results demonstrate the application potential of composite gels in meeting the performance maintenance and heat dissipation, which are needed for modern electronic devices. Abstract : A soft composite gel is developed through lengthening polymer strands and control fillers. The composite gel exhibits high toughness (4741.48 J m −2 ), excellent softness (low elastic modulus of 340 kPa), and low thermal resistance (0.14 cm 2 K W −1, under 10 psi pressure). Using this gel as a thermal interface material, effective heat dissipation is demonstrated in electronic devices.